Analisis Praktik Pengembangan Usaha Minimarket Berdasarkan Peraturan Walikota Palembang Nomor 25 Tahun 2011 Tentang Pedoman Penataan Dan Pembinaan Pusat Perbelanjaan Dan Toko Modern Dalam Perspektif Etika Bisnis Islam - fety vera (Medina-te : Jurnal Studi Islam, 2018)
The market competition in primary human need business lies in retail businesses that also experience competition. Retail or retail businesses are all activities involved in the sale of goods or services directly to the final consumer for personal and non-business use. As we know that business competition is a consequence of business actors, not excluding retail trade in Indonesia. The issues discussed here are the Government’s Role in the Regulation of Minimarket Business Areas and Lawlessness Committed by Minimarket Business actors in Palembang City. The formulation of the problem includes about how the development of minimarket based on the Regulation of the Mayor of Palembang Number 25 years 2011. The aim is to analyze the develpoment of minimarket based on Regulation of the Mayor of Palembang Number 25 years 2011 on the road Kapten Abdullah Kelurahan Plaju Ilir Kecamatan Seberang Ulu II Kota Palembang.